Contact With Young Children Increases the Risk of Respiratory Infection in Older Adults in Europe—the RESCEU Study. (15th December 2021) - Korsten, Koos; Adriaenssens, Niels; Coenen, Samuel; Butler, Chris C; Pirçon, Jean Yves; Verheij, Theo J M; Bont, Louis J; Wildenbeest, Joanne G; ,
Abstract: Background: Knowledge about how older adults get a respiratory infection is crucial for planning preventive strategies. We aimed to determine how contact with young children living outside of the household affects the risk of acute respiratory tract infections (ARTI) in community-dwelling older adults. Methods: This study is part of the European RESCEU older adult study. Weekly surveillance was performed to detect ARTI throughout 2 winter seasons (2017-2018, 2018-2019). Child exposure, defined as having regular contact with children under 5 living outside of the subject's household, was assessed at baseline. The average attributable fraction was calculated to determine the fraction of ARTI explained by exposure to these children. Results: We prospectively established that 597/1006 (59%) participants experienced at least 1 ARTI. Child exposure increased the risk of all-cause ARTI (adjusted odds ratio [aOR], 1.58; 95% confidence interval [CI], 1.21 -2.08; P = .001). This risk was highest in those with the most frequent contact (aOR, 1.80; 95% CI, 1.23-2.63; P = .003). The average attributable fraction of child exposure explaining ARTI was 10% (95% CI, 5%-15%). Conclusions: One of 10 ARTI in community-dwelling older adults is attributable to exposure to preschool children living outside of the household. Clinical Trials Registration: NCT03621930.